EBV DNA increase in COVID-19 patients with impaired lymphocyte subpopulation count. (March 2021) - Paolucci, Stefania; Cassaniti, Irene; Novazzi, Federica; Fiorina, Loretta; Piralla, Antonio; Comolli, Giuditta; Bruno, Raffaele; Maserati, Renato; Gulminetti, Roberto; Novati, Stefano; Mojoli, Francesco; Baldanti, Fausto; et al.
Highlights: EBV reactivation was observed in patients with COVID-19. NK + and CD8 + T cell reduction was related to the severity of COVID-19 infection. An increase of B cells in patients with severe symptoms was documented. Abstract: Objectives: The immunologic profile and opportunistic viral DNA increase were monitored in Italian patients with COVID-19 in order to identify markers of disease severity. Methods: A total of 104 patients infected with SARS-CoV-2 were evaluated in the study. Of them, 42/104 (40.4%) were hospitalized in an intensive care unit (ICU) and 62/104(59.6%) in a sub-intensive care unit (SICU). Human cytomegalovirus (HCMV) and Epstein-Barr virus (EBV), Parvovirus B19 and Human Herpesvirus 6 virus reactivations were determined by real-time PCR, and lymphocyte subpopulation counts were determined by flow cytometry. Results: Among opportunistic viruses, only EBV was consistently detected. EBV DNA was observed in 40/42 (95.2%) of the ICU patients and in 51/61 (83.6%) of the SICU patients. Comparing the two groups of patients, the EBV DNA median level among ICU patients was significantly higher than that observed in SICU patients. In parallel, a significant reduction of CD8 T cell and NK count in ICU patients as compared with SICU patients was observed (p < 0.05). In contrast, B cell count was significantly increased in ICU patients (p = 0.0172). Conclusions: A correlation between reduced CD8 + T cells and NK counts, EBV DNA levels and COVID-19 severity was observed. Other opportunistic viral infections were not observed. The relationship between EBV load and COVID-19 severity should be further evaluated in longitudinal studies.